PREFERENSI DAN PERSEPSI WISATAWAN MANCANEGARA KE NUSA PENIDA, KLUNGKUNG - Dewa Ayu Putu Putri Krisnadewi; I Nyoman Sudiarta; I Ketut Suwena (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2020)
The increasing tourist attraction of tourists must be adjusted to the availability of tourism facilities, such as attractions, Facilities, Infratructure, Transportation, and Hospitality (AFITH). Therefore, tourism stakeholders are important to know what the tourists are interested in and preferred or better known for their preference. This research aims to determine the preferences and perception of foreign tourists when visiting Nusa Penida, Klungkung. The analysis techniques that used are quantitative descriptive with the calculation of cross and chi-square tabulation analysis and also use of Likert scale gauge to measure the perception of foreign tourists that visiting Nusa Penida, Klungkung. Respondents determined by an Accidental samplingtechnique 90 peoples of foreign tourists that visiting Nusa Penida, Klungkung. The characteristic of foreign tourists on this research dominated by male tourist in 26-35 years old, dominated by Germany’s tourist, with the education level dominated by bachelor, as an employee, and the status is single, which aims to holiday with a source of information on Internet/social media, long stay 3-4 days, first time visit, and expressed willing to visit Nusa Penida, Klungkung again in another opportunity. The preference of foreign tourists when visiting Nusa Penida is divided into several preferences such as tourist attractions are natural attractions, on the preferences of accommodation facilities, foreign tourists choose a homestay, and then the tourist prefer to choose a warung or traditional stalls, and the transportation that choosen by the tourist is motorcycle. Perception of tourists to infrastructure that includes network communication and availability of clean water, the perception of tourists to the road conditions in Nusa Penida is not good, perception of tourists towards Hospitality in tourist attractions, Hospitality in the accommodation, and local community Hospitality expressed well.